The relationship between quality training practices and internal customer satisfaction: An empirical study in Malaysian local authorities / Khairul Anuar Mohd Ali - Mohd Ali, Khairul Anuar (2004)
This study examines the relationship between quality training practices and the internal customer satisfaction of the local authorities in Peninsular Malaysia. Three hundred twenty managers from eighty organizations participated in this study. Disproportionate stratified random sampling was used as the sampling technique from the population frame and the data were gathered through self administered structured questionnaires. Employing regression analysis, the results revealed that quality training practices has positive association with the internal customer satisfaction. Thus, in order to achieve superior level of internal customer satisfaction, the local authorities need to address correspondingly to the issue.